+0  
 
0
48
1
avatar+272 

Let A(t) = 3- 2t^2 + 4^t. Find A(2) - A(1).

 

The function f satisfies f(sqrt(x+1)) = 1/x for all $x >= -1, x does not equal 0. Find f(2).

 

Thanks :D

WhichWitchIsWhich  Oct 29, 2017

Best Answer 

 #1
avatar+5229 
+1

A(t)  =  3 - 2t2 + 4t

 

A(2)  =  3 - 2(2)2 + 42

 

A(1)  =  3 - 2(1)2 + 41

 

A(2) - A(1)  =  [ 3 - 2(2)2 + 42 ] - [ 3 - 2(1)2 + 41 ]

 

A(2) - A(1)  =  [ 3 - 2(4) + 16 ] - [ 3 - 2(1) + 4 ]

A(2) - A(1)  =  [ 3 - 8 + 16 ] - [ 3 - 2 + 4 ]

A(2) - A(1)  =  [ 11 ] - [ 5 ]

A(2) - A(1)  =    6

 

----------

 

f( √[x + 1] )  =  1/x      for  x ≥ -1  and  x ≠ 0  

 

We want to find  f(2)  , so we need an x value that makes

 

√[ x + 1]  =  2      square both sides

x + 1  =  4           subtract  1  from both sides

x  =  3                 This is a valid  x  to plug in.

 

So....

 

f( √[3 + 1] )  =  1/3

f( 2 )  =  1/3                 smiley

hectictar  Oct 29, 2017
Sort: 

1+0 Answers

 #1
avatar+5229 
+1
Best Answer

A(t)  =  3 - 2t2 + 4t

 

A(2)  =  3 - 2(2)2 + 42

 

A(1)  =  3 - 2(1)2 + 41

 

A(2) - A(1)  =  [ 3 - 2(2)2 + 42 ] - [ 3 - 2(1)2 + 41 ]

 

A(2) - A(1)  =  [ 3 - 2(4) + 16 ] - [ 3 - 2(1) + 4 ]

A(2) - A(1)  =  [ 3 - 8 + 16 ] - [ 3 - 2 + 4 ]

A(2) - A(1)  =  [ 11 ] - [ 5 ]

A(2) - A(1)  =    6

 

----------

 

f( √[x + 1] )  =  1/x      for  x ≥ -1  and  x ≠ 0  

 

We want to find  f(2)  , so we need an x value that makes

 

√[ x + 1]  =  2      square both sides

x + 1  =  4           subtract  1  from both sides

x  =  3                 This is a valid  x  to plug in.

 

So....

 

f( √[3 + 1] )  =  1/3

f( 2 )  =  1/3                 smiley

hectictar  Oct 29, 2017

16 Online Users

avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details